Respuesta :

Answer:

(2, 5 )

Step-by-step explanation:

Given the 2 equations

3x + 2y = 16 → (1)

2x + y = 9 → (2)

Multiplying (2) by - 2 and adding to (1) will eliminate the y- term

- 4x - 2y = - 18 → (3)

Add (1) and (3) term by term to eliminate y

- x = - 2 ( multiply both sides by - 1 )

x = 2

Substitute x = 2 into either of the 2 equations and solve for y

Substituting into (1)

3(2) + 2y = 16

6 + 2y = 16 ( subtract 6 from both sides )

2y = 10 ( divide both sides by 2 )_

y = 5

solution is (2, 5 )

ACCESS MORE